CLINICAL IMMUNOLOGICAL PECULIARATIES OF ATOPIC BRONCHIAL ASTHMA DEPENDING FROM THE LEVEL OF CONTROL OVER THE DISEASE IN CHILDREN - O. S. Tyutina; S. V. Smirnova; M. V. Smolnikova; N. A. Ilyenkova (Acta Biomedica Scientifica, 2012)
The formation of definite phenotype in atopic bronchial asthma is associated with interaction between environment factors and peculiarities of endogenous constitution. We have carried out the analysis of peculiarities of immunological status, cytokine regulation of cellular interactions collectively with environment factors. We have revealed the predictors of non-controllable course of atopic bronchial asthma in children.